Long-Term Care Policies for Older Populations in New EU Member States and Croatia : Challenges and Opportunities - World Bank (Washington, DC, 2013)
The objective of this summary report is to highlight the main lessons learned from Organization for Economic Development and Co-operation (OECD) countries with advanced Long Term Care (LTC) policies and the implications for LTC policymaking in new European Union (EU) member states and Croatia. The first section examines the main findings from the framework report on the financing, provision and regulation of LTC services. The next section presents comparative findings from the four case study countries, including the demographic context for LTC services, the main features of the financing, provision and regulation of LTC services and the strengths and weaknesses of current LTC systems there. The last section identifies policy directions for the four case study countries. In terms of LTC benefits, none of the case study countries have a universal entitlement system combining home, community and institutional care. Rather, LTC benefits, both cash and in-kind, are limited and largely associated with the social assistance system. The lack of data on LTC expenditures mainly stems from the undefined position of LTC between the health and social sectors, which makes it difficult to accurately collect data.